Uncontrolled urban vegetable farming poses public health risks in Ethiopia - Addis, Taffere; Ketema, Sisay; Melaku, Abayneh (Frontiers in Water, 2025)
Urban agriculture is increasingly recognized as a vital part of food security initiatives in cities worldwide, including Addis Ababa, Ethiopia. We studied trace metal levels in sediment, soil and irrigated vegetables from farms located along the Akaki River in Addis Ababa, Ethiopia’s capital, and evaluated the associated public health risks. A total of 24 sediment and 36 soil samples, and edible parts of most widely cultivated vegetables were collected and analyzed for trace metals content using an Inductively Coupled Plasma Mass Spectrometry (ICP-MS). In sediment samples, the contents of As, Cr, Cu, Ni, Pb, and Zn were above the threshold effect level. Soil levels of As, Cr, Cu, Mn, and Zn levels exceeded typical values of world soils. Besides, Ni soil content at one farming site exceeded the limits set by the European Economic Community (EEC) for agricultural soils. Strikingly, the levels of As, Pb, and Zn in few vegetable samples were above the allowable limits of the World Health Organization (WHO) despite the fact that the levels of these metals in the soil samples were within the acceptable ranges for agricultural soils. Therefore, the allowable concentrations of trace elements in agricultural soils may need to be more stringent. Cadmium, a known cause for kidney, bone, and lung diseases including cancer, was the most accumulated in vegetables. Among the toxic metals, the levels of As, Cr, and Pb were higher in Swiss chard samples. The irrigation water quality and consumption of vegetables cultivated in such urban soils may also need to be restricted.